How aggressive should resection of inverted papilloma be? Refinement of surgical planning based on the 25‐year experience of a single tertiary center. Issue 5 (28th February 2020) - Ferrari, Marco; Schreiber, Alberto; Mattavelli, Davide; Rampinelli, Vittorio; Bertazzoni, Giacomo; Tomasoni, Michele; Gualtieri, Tommaso; Nicolai, Piero
Abstract : Background: The technique for transnasal endoscopic resection of inverted papilloma (IP) has evolved considerably during the last 20 years. The aim of the present study is to retrospectively analyze a single tertiary center series, with special emphasis on assessing the value of an "insertion‐driven" technique on local control. Methods: Patients undergoing endoscopic resection for IP at the University of Brescia during the period 1991 to 2015 were enrolled. Site of origin and extension of IPs were assessed, together with presence of dysplasia and carcinoma in situ. Patients were divided in 3 cohorts: (1) historical cohort (treated before 2008), (2) contemporary "centripetal" cohort (treated with a traditional technique after 2008), and (3) contemporary "insertion‐driven" cohort (treated with insertion‐driven resection). Groups were compared considering outcomes and complications. Results: The series included 210 patients. Mean follow‐up was 77.8 months. Thirty‐eight (18.1%) patients showed precancerous changes. Maxillary involvement ( p = 0.021) and presence of precancerous changes ( p = 0.013) were significantly associated with a higher risk of recurrence. Five‐year local control rate before and after 2008 was 95.1% and 90.5%, respectively. The insertion‐driven cohort was associated with lower disease control when IPs involved the maxillary sinus. The rate of complications was 11.9%. The insertion‐driven cohort was associated with a lower rate of major complications ( p = 0.098). Conclusion: Preoperative evidence of precancerous changes and/or involvement of maxillary sinus should prompt the surgeon to address the disease more aggressively (centripetal resection). Preoperative imaging and biopsy with abundant material may optimize the chance to stratify patients eligible for less or more conservative approaches.